Single-Loop Projection-Free and Projected Gradient-Based Algorithms for Nonconvex-Concave Saddle Point Problems with Bilevel Structure - Ahmadi, Mohammad Mahdi; Yazdandoost Hamedani, Erfan (Journal of scientific computing, 2025)
In this paper, we explore a broad class of constrained saddle point problems with a bilevel structure, wherein the upper-level objective function is nonconvex-concave and smooth over compact and convex constraint sets, subject to a strongly convex lower-level objective function. This class of problems finds wide applicability in machine learning, encompassing robust multi-task learning, adversarial learning, and robust meta-learning. Our study extends the current literature in two main directions: (i) We consider a more general setting where the upper-level function is not necessarily strongly concave or linear in the maximization variable. (ii) While existing methods for solving saddle point problems with a bilevel structure are projected-based algorithms, we propose a one-sided projection-free method employing a linear minimization oracle. Specifically, by utilizing regularization and nested approximation techniques, we introduce a novel single-loop one-sided projection-free algorithm, requiring O ( ϵ - 4 ) iterations to attain an ϵ -stationary solution, moreover, when the objective function in the upper-level is linear in the maximization component, our result improve to O ( ϵ - 3 ) . Subsequently, we develop an efficient single-loop fully projected gradient-based algorithm capable of achieving an ϵ -stationary solution within O ( ϵ - 5 ) iterations. This result improves to O ( ϵ - 4 ) when the upper-level objective function is strongly concave in the maximization component. Finally, we tested our proposed methods against the state-of-the-art algorithms for solving a robust multi-task regression problem to showcase the superiority of our algorithms.